Analisis Yuridis Normatif Kebijakan Pubik Penanggulangan Prostitusi - Rahajaan, Jakobus Anakletus; Niapele, Sarifa (Public Policy, 2023)
Prostitution is a classic problem that is very complex and full of dynamics. Prostitution is a criminogenic phenomenon that should be taken seriously because it causes a domino effect such as the emergence of criminality in the middle of society. Prostitution has a far-reaching impact on the values of the lives and futures of the younger generation. This study aims to analyze the public policies of the Ambon city government in the context of tackling prostitution in the city of Ambon. For this reason, with normative juridical research methods, the results of our research found that the public policy of the Ambon city government in the Forma Perda is no longer relevant to the social dynamics of society, especially with the dynamics of prostitution which is now shifting from official or direct prostitution (localization) to the era of unofficial online prostitution and more complex problems. While the public policy in the forma of the mayor's decree on the closure of the localization of the red rock cape of Ambon, is limited in nature and does not contain criminal content material so that although it has been officially closed, it still operates clandestinely or covertly. The conclusion is that official prostitution in the city of Ambon has been juridically prohibited.but the elimination of unofficial or illegal prostitution either through direct transactions or online transactions, is not effective and efficient. So we recommend that public policy makers in Ambon city can be serious and immediately make specialist and specific policies to tackle the problem of prostitution effectively and efficiently.